Factors associated with the introduction of prelacteal feeds in Nepal: findings from the Nepal Demographic and Health Survey 2011 - Khanal, Vishnu; Adhikari, M.; Sauer, Kay; Zhao, Yun (BioMed Central, 2013)
Background: A prelacteal feed is any food except mother’s milk provided to a newborn before initiating breastfeeding. Prelacteal feeding is a major barrier to exclusive breastfeeding. It is a prevalent practice in Nepal. Little is known about the factors associated with providing prelacteal feeds to the Nepalese newborn. This study explored the factors associated with providing prelacteal feeds to children under three years in Nepal using the Nepal Demographic and Health Survey (NDHS) 2011. Methods: This study utilised the NDHS 2011 child dataset which is a nationally representative study. The rates of providing prelacteal feeds were reported as a proportion. Complex Sample Analysis method was used to account for the cluster design and sample weight of the study. Chi-square tests and multiple logistic regression were used to analyse the factors associated with providing prelacteal feeds.Results: A sample of 3948 mothers were included in the study. A total of 841 [26.5% (95% CI: 23.1%–30.3%)] weighted proportion) of mothers reported of providing prelacteal feeds to their newborn infants. Plain water (n = 75), sugar/glucose (n = 35), gripe water (n = 3), sugar/salt solution (n = 3), fruit juice (n = 3), infant formula (n = 96), tea (n = 3) and other milk other than breast milk (n = 556) were some of the types of prelacteal feeds reported. The multiple regression analysis showed that the mothers who had no education, were not working, were from the middle wealth quintile, who had not attended four antenatal care visits, were first time mothers and who were from the Terai/Plain region were more likely to provide prelacteal feeds. Conclusions: Given that one in four infants were provided with prelacteal feeds, there is a need to implement breastfeeding promotion programs to increase the practice of exclusive breastfeeding and reduce prelacteal feeding practices. Breastfeeding counseling at antenatal clinics and peer support for exclusive breastfeeding should be included as part of breastfeeding promotion programs. Mobilisation of female community health volunteers for peer counseling is also a feasible option for Nepal.